High Graft CD8 Cell Dose Predicts Improved Survival and Enables Better Donor Selection in Allogeneic Stem-Cell Transplantation With Reduced-Intensity Conditioning - Reshef, Ran (J Clin Oncol, 2015)
PURPOSE: To characterize the impact of graft T-cell composition on outcomes of reduced-intensity conditioned (RIC) allogeneic hematopoietic stem-cell transplantation (alloHSCT) in adults with hematologic malignancies. PATIENTS AND METHODS: We evaluated associations between graft T-cell doses and outcomes in 200 patients who underwent RIC alloHSCT with a peripheral blood stem-cell graft. We then studied 21 alloHSCT donors to identify predictors of optimal graft T-cell content. RESULTS: Higher CD8 cell doses were associated with a lower risk for relapse (adjusted hazard ratio [aHR], 0.43; P = .009) and improved relapse-free survival (aHR, 0.50; P = .006) and overall survival (aHR, 0.57; P = .04) without a significant increase in graft-versus-host disease or nonrelapse mortality. A cutoff level of 0.72 × 10(8) CD8 cells per kilogram optimally segregated patients receiving CD8(hi) and CD8(lo) grafts with differing overall survival (P = .007). Donor age inversely correlated with graft CD8 dose. Consequently, older donors were unlikely to provide a CD8(hi) graft, whereas approximately half of younger donors provided CD8(hi) grafts. Compared with recipients of older sibling donor grafts (consistently containing CD8(lo) doses), survival was significantly better for recipients of younger unrelated donor grafts with CD8(hi) doses (P = .03), but not for recipients of younger unrelated donor CD8(lo) grafts (P = .28). In addition, graft CD8 content could be predicted by measuring the proportion of CD8 cells in a screening blood sample from stem-cell donors. CONCLUSION: Higher graft CD8 dose, which was restricted to young donors, predicted better survival in patients undergoing RIC alloHSCT.